Creating an Integrated Curriculum The 'Higher' In Higher Education. 1981 Current Issues in Higher Education, No. 2. - American Association for Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Perspectives on creating an integrated college curriculum are presented in four papers. In "What is 'Higher' About Higher Education?" Harlan Cleveland suggests that colleges and universities should promote a global view and understanding of problems on society and international interdependence and should develop the capacity to analyze and integrate knowledge from academic disciplines and specialized training to help solve real-world problems. In "Curricular Integration: Mortar for the Ivory Tower," Mary Jim Joseph suggests that interdisciplinary courses and programs are a necessary but not sufficient provision in an overall curricular structure designed to assure integration. Skills development is a major tool of integration, and other options for creating curricular integration include integration within general education, majors, field study, and electives. In "Integrative General Education: The Saint Joseph's Model," John Nichols describes the development and implementation of a core curriculum at Saint Joseph's College, Indiana. The 45-credit program in general education was adopted in 1968 and is interdisciplinary, integrative, and team-taught. The content of the 10 cores and core objectives are identified. In "An Integrative Program for Building Skills: The City and the Self," Susan Gurewitsch describes an integrative program for freshmen at Albertus Magnus College, Connecticut, which is designed to build skills such as observation, synthesis, and problem-solving, along with reading and writing skills. A seminar in thought and expression and short courses in the humanities, social sciences, and natural science or mathematics are based on a student-centered approach, which involves lecture, discussion, and field work. (SW)
Availability: American Association for Higher Education, One Dupont Circle, Suite 600, Washington, DC 20036 ($3.50 plus postage and handling).
ERIC Note: Selected papers presented at the Annual National Conference of the American Association for Higher Education (Washington, DC, March 1981).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Curriculum; College Freshmen; Core Curriculum; General Education; Global Approach; Higher Education; Humanities; Interdisciplinary Approach; Logical Thinking; Natural Sciences; Reading Skills; Skills; Social Sciences; Student Needs; Albertus Magnus College CT -- Saint Josephs College IN; Collected Works, Proceedings; Opinion Papers; Reports, Descriptive